(3LGeY GdeHGOF hGdZGjGJ aj Yde GdejbGJs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3JHJOF HGdaUd GdNGeS hGdYTQjf ef Gdaf GdKGfi , Hbhdg (B: (3ai eYQaI eOGQ Ci LRA TFJ cja QSeg GdXd ai Ci hbJ TFJ s
(3BNQgG (B:s
(3ef Gdaf GdQGHY , bhdg (B: (3aHbi OQLI hGMOI ce cGf GdXd hce cGf GdJYOjd hgh GdXd GdeWdhH hHGbi GdYed XGgQ hef CMGW YdekG HeG PcQJg ef GdeSGFd CYfi WQjb GdLHQ hGdebGHdI , hGddg Gdehab ddUhGH s
(3HgG CTcGds
(3GdJUhjQ ZjQ fGLM ai ehGVY cKjQIs
(3HgG fXGe GdJYbjHIs
(3hgh CYXe eG Ufa ai gPG Gdafs
(3LRA efg s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs